Concentrate management for nf brine of ground water using electromembrane (ED and EDI) processes - Altıok, Esra; Bunani, Semyuel; İpekçi, Deniz; Kabay, Nalan; Arda, Muserref; Yüksel, Mithat (My University, 2016)
In this study, treatment of ground water used in a fruit juice company located in İzmir city by integrated nanofiltration (NF), electrodialysis (ED) and electrodeionization (EDI) methods was studied. For this purpose, the ground water obtained from the plant was treated by using two different NF membranes (NF-90 and NF-270). The brine from both NF membranes was fed to ED stack. The ED diluate was further treated by EDI process for ultrapure water production.
Keywords: concentrate management; food industry; nanofiltration; electrodialysis; electrodeionization; water reuse; безперервна переробка; харчова промисловість; нанофільтрація; електродіаліз; електродеіонізація; повторне використання води; непрерывная переработка; пищевая промышленность; нанофильтрация; электродиализ; электродеионизация; повторное использование воды